Ag Atom Anchored on Defective Hexagonal Boron Nitride Nanosheets As Single Atom Adsorbents for Enhanced Adsorptive Desulfurization via S-Ag Bonds - Hui Liu; Jie Yin; Jinrui Zhang; Hongshun Ran; Naixia Lv; Wei Jiang; Hongping Li; Wenshuai Zhu; Huaming Li (Nanomaterials, 2022)
Single atom adsorbents (SAAs) are a novel class of materials that have great potential in various fields, especially in the field of adsorptive desulfurization. However, it is still challenging to gain a fundamental understanding of the complicated behaviors on SAAs for adsorbing thiophenic compounds, such as 1-Benzothiophene (BT), Dibenzothiophene (DBT), and 4,6-Dimethyldibenzothiophene (4,6-DMDBT). Herein, we investigated the mechanisms of adsorptive desulfurization over a single Ag atom supported on defective hexagonal boron nitride nanosheets via density functional theory calculations. The Ag atom can be anchored onto three typical sites on the pristine h-BN, including the monoatomic defect vacancy (B-vacancy and N-vacancy) and the boron-nitrogen diatomic defect vacancy (B-N-divacancy). These three Ag-doped hexagonal boron nitride nanosheets all exhibit enhanced adsorption capacity for thiophenic compounds primarily by the S-Ag bond with π-π interaction maintaining. Furthermore, from the perspective of interaction energy, all three SAAs show a high selectivity to 4,6-DMDBT with the strong interaction energy (−33.9 kcal mol−1, −29.1 kcal mol−1, and −39.2 kcal mol−1, respectively). Notably, a little charge transfer demonstrated that the dominant driving force of such S-Ag bond is electrostatic interaction rather than coordination effect. These findings may shed light on the principles for modeling and designing high-performance and selective SAAs for adsorptive desulfurization.